This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
The mean proportional of two numbers is the same as the geometric mean of the the two numbers.

Geometric mean of two numbers x and y =  \sqrt{xy}

So mean proportional of a - b and a³ - a²b is 

 =\sqrt{(a-b)(a^3-a^2b)} \\= \sqrt{(a-b)*a^2(a-b)}\\ = \sqrt{a^2*(a-b)^2} \\=\boxed{a(a-b)}